Profil Kebutuhan Pengasuhan Anak pada Pasangan Muda - Nurul Hidayah; Nissa Tarnoto; Ega Asnatasia Maharani (Jurnal Ilmu Perilaku, 2018)
Nowadays, there are many married couples in Indonesia who have not unable to nurture their children effectively. This study aims at developing curriculum on child nurturing for young couples to optimize their children’s growth. The implementation of the research will be done in multiyear. In the first year, the focus will be on the needs assessment on young couples related to some important issues. The subjects of the research will be 132 parents aged up to 30 years old who have been married for up to 5 years. The place of the research will be in four districts in DIY with focus group discussion (FGD) method as the main instrument. The FGD will be applied with Rapid Rural Appraisal (RRA) method. Data analysis using thematic analysis. The results showed that the profile of the young couple's needs on parenting consisted of five aspects: (1) the nurturing dimension consisting of physical, cognitive, and affective dimensions; (2) self-centered, child-centered, and parent-child parenting goals; (3) forms of care in the form of demand, control, response, and acceptance; (4) framework which includes nuclear family and extended family; and (5) how to overcome both internal and external parenting barriers.